Synthesis of Arylidenehydrazinyl‐4‐methoxyphenylthiazole Derivatives: Docking Studies, Probing Type II Diabetes Complication Management Agents. Issue 11 (26th October 2022) - Mehmood, Hasnain; Akhtar, Tashfeen; Haroon, Muhammad; Tahir, Ehsaan; Ehsan, Muhammad; Woodward, Simon; Musa, Mustapha
Abstract: Thiazole has been a key scaffold in antidiabetic drugs. In quest of new and more effective drugs a simple, efficient, high yielding (67–79 %) and convenient synthesis of arylidenehydrazinyl‐4‐methoxyphenyl)thiazoles is accomplished over two steps. The synthesis involved the condensation of aryl substituted thiosemicarbazones and 2‐bromo‐4‐methoxyacetophenone in absolute ethanol. The structures of the resulting thiazoles are in accord with their UV/VIS, FT‐IR, 1 H‐, 13 C‐NMR and HRMS data. All compounds were evaluated for alpha(α)‐amylase inhibition potential, antiglycation, antioxidant abilities and biocompatibility. The compounds library identified 2‐(2‐(3, 4‐dichlorobenzylidene)hydrazinyl)‐4‐(4‐methoxyphenyl)thiazole as a lead molecule against α‐amylase inhibition with an IC50 of 5.75±0.02 μM. α‐Amylase inhibition is also supported by molecular docking studies against α‐amylase. All the obtained thiazoles also showed promising antiglycation activity with 4‐(4‐methoxyphenyl)‐2‐2‐[2‐(trifluoromethyl)benzylidene]hydrazinylthiazole exhibiting the best inhibition (IC50 = 0.383±0.001 mg/mL) compared to control. The tested compounds are also biocompatible at the concentration used i. e., 10 μM. Abstract :